2014
DOI: 10.1111/ajt.12851
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Foxp3+ T Cells Abrogates Tolerance of Skin and Heart Allografts in Murine Mixed Chimeras Without the Loss of Mixed Chimerism

Abstract: The relative contribution of central and peripheral mechanisms to the generation and maintenance of allograft tolerance is of considerable interest. Here, we present new evidence that regulatory T cells (Foxp3+) maintain skin and heart allograft tolerance in mixed hematopoietic chimeric mice. Transient depletion of both donor‐ and recipient‐derived Foxp3+ cells was necessary and sufficient to induce decisive rejection of long‐accepted skin and heart allografts. In contrast, stable hematopoietic chimerism remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…þ Tregs were required to maintain skin-and cardiac-allograft tolerance even in the chimeras (34,35). However, this late-phase rejection was also observed even when whole CD4 þ T cells including CD4 þ CD25 þ Tregs were transferred into SCID mice (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…þ Tregs were required to maintain skin-and cardiac-allograft tolerance even in the chimeras (34,35). However, this late-phase rejection was also observed even when whole CD4 þ T cells including CD4 þ CD25 þ Tregs were transferred into SCID mice (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…HLA identity may be advantageously assessed, eliminating variability of immune response genes associated with donor/recipient specific HLA polymorphisms. Additionally, immunoregulation (Tregs) may be aided by self-recognition by the recipient of both donor major histocompatibility complexes (MHC) (12, 13). We described earlier in a brief communication (10) 3-year results of a tolerance protocol in 10 RT recipients HLA identical with their living donor siblings using 4 infusions of donor hematopoietic stem cells (DHSC).…”
Section: Introductionmentioning
confidence: 99%
“…Uehara et al reported that skin and heart allografts accepted by mice displaying stable mixed chimerism later developed cardiac allograft vasculopathy (chronic rejection) dependent on the presence of host CD4 + T cells [24]. More recently, Shinoda et al found that depleting Foxp3 + T cells abrogated tolerance of skin and heart allografts in stable mixed chimeras without an associated loss of mixed chimerism [25]. Of note, the authors here found that host T cells collected from the rejecting mice were unable to mount a mixed lymphocyte reaction against donor cells.…”
Section: Introductionmentioning
confidence: 99%
“…The latter finding indicates that rejection in these animals was not mediated by T cells directed against intact allogeneic MHC molecules on donor APCs. In other words, it did not involve direct allorecognition [25]. Instead, it is likely that the T cells causing rejection were directed toward cryptic determinants on donor MHC, minor antigens, or graft tissue-specific antigens presented in an indirect fashion, as previously described [26-29].…”
Section: Introductionmentioning
confidence: 99%